Application of the McMurry Coupling Reaction in the Synthesis of Tri- and Tetra-arylethylene Analogues as Potential Cancer Chemotherapeutic Agents - Tanpure, Rajendra P. (2009)
Structural redesign of selected non-steroidal estrogen receptor binding compounds has previously been successful in the discovery of new inhibitors of tubulin assembly. Accordingly, tetra-substituted alkene analogues (21-30) were designed based in part on combinations of the structural and electronic components of tamoxifen and combretastatin A-4 (CA4). The McMurry coupling reaction was used as the key synthetic step in the preparation of these tri- and tetra-arylethylene analogues. The structural assignment of E, Z isomers was determined on the basis of 2D-NOESY experiments. The ability of these compounds to inhibit tubulin polymerization and cell growth in selected human cancer cell lines was evaluated. Although the compounds were found to be less potent than CA4, these analogues significantly advance the known structure activity relationship associated with the colchicine binding site on β-tubulin.